BENTUK FATIS DALAM BAHASA MELAYU BANGKA - Rahmat Muhidin (﻿Kantor Bahasa Provinsi Bangka Belitung, 2013)
Form of fatis is sign of communication nonformal varians.This paper used linguistic theory with descriptivemethod. This paper will describe the forms of fatis in Bangka Malays. Signed of fatis varians in the BangkaMalays: ah (afektif reject), ayo (let’s), ok (agreement), kek (to make an imperative sentence more polite), mari(come on), and lah (already) and ya (yes, agreement).